2018
DOI: 10.1007/s13197-018-3355-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vivo antioxidant potential of Syzygium jambos (L.) Alston and Terminalia citrina Roxb. towards oxidative stress response in Saccharomyces cerevisiae

Abstract: Excessive production and restricted elimination of free radicals like superoxide, hydroxyl radical (Á OH), anion radical (O 2 Á-), and non-radical hydrogen peroxide (H 2 O 2) are related to the development of cancer, arteriosclerosis, arthritis and neurodegenerative diseases. According to a report of World Health Organisation, about 80% of the population living in the developing countries predominantly depends on the traditional medicine for their primary healthcare. Plants possess innate ability to synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…The ROS model has been well studied at present, mainly because ROS production promotes the dissociation between thioredoxin in cells and its ligand in Txnip, the latter of which may bind to NLRP3 and lead to its activation (37). Oxidative stress is caused by the imbalance between antioxidants and ROS, and its effect of promoting AS has been widely recognized (38). Studies have demonstrated that ROS significantly promotes the occurrence and development of AS (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…The ROS model has been well studied at present, mainly because ROS production promotes the dissociation between thioredoxin in cells and its ligand in Txnip, the latter of which may bind to NLRP3 and lead to its activation (37). Oxidative stress is caused by the imbalance between antioxidants and ROS, and its effect of promoting AS has been widely recognized (38). Studies have demonstrated that ROS significantly promotes the occurrence and development of AS (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Terminalia bellirica, Terminalia citrina, Tinospora crispa, and Zingiber officinale. All its herbal components, except for Maerua siamensis, have been found to act as free radical scavengers, [29][30][31][32][33][34][35][36] © 2021 the authors. This work is licensed under the Creative Commons Attribution 4.0 International License thereby playing the main role in the reactive oxygen species scavenging activities of Phy-Blica-O.…”
Section: Preliminary Antioxidant Activity Resultsmentioning
confidence: 99%
“…Among these, the administration of extracts obtained from Allium sativum, Zingiber officinale, Piper retrofractum, Terminalia citrina, Terminalia bellirica, Phyllanthus emblica, Tinospora crispa, or Terminalia arjuna has been found to attenuate the antioxidant status in animal models. 31,34,35,[37][38][39][40][41][42] Clinical studies have also revealed that Phyllanthus emblica or Terminalia arjuna consumption significantly changes the oxidative stress biomarkers in patients. 43,44 Although Phy-Blica-O is made by combining equal amounts of the medicinal plant, it is likely that Phyllanthus emblica and Terminalia arjuna were its active ingredients, according to the evidence mentioned above…”
Section: Preliminary Antioxidant Activity Resultsmentioning
confidence: 99%
“…This approach may lead to reduced pathogenicity of pathogens and a reduction in the development of resistance (Silva et al, 2016). Indeed, the ability of a pathogenic bacterium to form biofilm communities and to move across surfaces is very important for virulence determination (Kearns, 2010;Rajkumari et al, 2018b). Interestingly, our extract at sub-inhibitory concentrations (1/ 8 MIC = 12.5 mg/mL and 1/4 MIC = 25 mg/mL) significantly reduced the amount of the biofilm produced with inhibition percentages of 41.17% and 88.23%, respectively (Figure 10B).…”
Section: Antibacterial Activitiesmentioning
confidence: 99%